If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-4 + 5x) = 93 (-4 * 3 + 5x * 3) = 93 (-12 + 15x) = 93 Solving -12 + 15x = 93 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 15x = 93 + 12 Combine like terms: -12 + 12 = 0 0 + 15x = 93 + 12 15x = 93 + 12 Combine like terms: 93 + 12 = 105 15x = 105 Divide each side by '15'. x = 7 Simplifying x = 7
| 7(w-76)=77 | | 3+4g=19 | | 200+.5=400 | | 2=16-2c | | 3(-3+x)=-9 | | 5+3t=17 | | 8x-5(5-3)=18 | | 12=8+2j | | -2(5-4x)=54 | | 2x-x^2=-25-10 | | 6=2+2c | | 7(4-5x)=308 | | 8a^2-56a=0 | | 3(7x-5)=174 | | 9y-11-4y+8=0 | | 6(3+4x)=-3 | | -3(x-5)=2(-2x-6)+6 | | 3(9+7x)=27 | | x=-9(.5)-1 | | 3(7-6x)=21 | | 140n^2=-36nZ+8 | | -3(4+6x)=-48 | | x+9y=-1 | | --3(4r-8)=-36 | | -2X+3X=-25 | | -8x-6=3x+27 | | 6(9+2x)=78 | | 7y-(3y+12)=8-(5y-2) | | 6(-2x-8)=-48 | | -62+11y+6=5(3-5)-7 | | 4ab^2/-20a^3b | | -15n+18=-13n-12 |